Synthesis and characterization of a multi-sensitive polysaccharide hydrogel for drug delivery. (1st December 2017) - Wei, Wei; Li, Junjian; Qi, Xiaoliang; Zhong, Yin; Zuo, Gancheng; Pan, Xihao; Su, Ting; Zhang, Jianfa; Dong, Wei
Highlights: A smart polysaccharide hydrogel was synthesized and characterized for drug delivery. Semi-IPN technique was used to keep properties of both polymers. Hydrogel sensitive to temperature, pH, and ionic strength. The hydrogel is cell compatible. Drug release rates can be controlled. Abstract: Salecan is a novel water soluble polysaccharide produced by a salt-tolerant strain Agrobacterium sp. ZX09. Poly(dimethylaminoethyl methacrylate) (PDMAEMA) is a pH, thermo, and ionic strength multi-sensitive polymer with anti-bacterial property. Here, we report a semi-interpenetrating polymer network (semi-IPN) hydrogel based on salecan and PDMAEMA. The obtained hydrogel is simultaneous sensitive to pH, ionic strength and temperature: the swelling ratio maximizes at pH 1.2 and shrinks at pH value greater than 3; besides, water content of the hydrogel decreases as the ionic strength increases; in terms of temperature, the hydrogel swells/deswells at temperatures below/above 40 °C. Cytotoxicity test shows the hydrogel is non-cytotoxic to COS-7 cells. Protein drug insulin was selected as model drug to test the in vitro release behavior of the hydrogel. Results show the release rate increases with the swelling ratio of the hydrogel. In addition, when the temperature is higher than the lower critical solution temperature (LCST) of PDMAEMA, the hydrogel shrinks to extrude more drug molecules. Moreover, the release rate and release amount were higher in acid condition (pH 1.2) than at pH 7.4. In summary, this polysaccharide hydrogel is a promising material for drug delivery.